Comparative Morphological Studies on the Harderian Gland in Pratapdhan and Kadaknath (Gallus gallus domesticus) Birds - Kumari, Mamta; Meshram, Balwant; Joshi, Hemant; Singh, Gajendra (Indian Journal of Veterinary Anatomy, 2023)
Avians Harderian Gland (HG) plays an important role in accomplish the local and systemic immunity and also to have immuno-defence responses against pathogens. The harderian gland, also known as the orbital gland, was located ventromedially around the posterior part of the eyeball and extended dorsal to it. It was observed near the inter-orbital septum of the orbit, between the medial straight muscle, pyramidal third eyelid muscle and ventral oblique muscle. Shape of HG in both Pratapdhan and Kadaknath birds was bi-lobed and resembling with a dumbbell or hour glass shape but the anterior end of gland was convex. No bifurcation was noticed in Pratapdhan bird, however, bifurcation was observed in Kadaknath birds. After removing the thin layer of fat, the glands in Pratapdhan birds showed pale pink colour whereas, the Kadaknath birds the gland was dark black coloured. The excretory duct of the HG was passing around the eyes. It was opened into the anterior lower portion of the conjunctiva! sac under the nictitating membrane.